AVIAN SPECIES COMPOSITION PROFILE AND FEEDING GUILDS UNDER THE AEROBIC RICE FIELD - Amzah, Badrulhadza; Baki, Razali; Yahya, Mohd Hafizi (Universitas Lampung, 2021)
Avian species composition profile and feeding guilds under the aerobic rice field. In Malaysia, the aerobic rice productionsystem is an alternative approach to growing rice in a water-scarce environment. Like irrigated rice, aerobic rice also cansustain a diversity of avian fauna. The current status of birds in the rice fields of Malaysia especially under aerobic ricecondition has not been widely researched. Therefore, this study aims to document the richness, diversity and feeding guildsof bird species in aerobic rice cultivation area. Birds were sampled and recorded using four randomly set up mist net at anupscaling aerobic rice plot in Serdang, Selangor during a period of the one month starting from the milky stage of the plant (75days after emergence) until two weeks after harvest. 139 birds representing 11 species belonging to 7 families were recordedin the aerobic rice plot. The most abundant bird family observed was Estrildidae (80.58%), followed by Hirundinidae (6.47%),and Meropidae and Motacillidae (both recorded 5.04%). Scaly-breasted munia (50.36%) and white-headed munia (28.06%) arethe most abundant birds, while other types of munia such as chestnut munia and white-rumped munia are present in smallnumbers. Munias were the most observed bird species number (36.36%) and therefore can be considered as the main avianpest of aerobic rice. The diversity indices, The Shannon-Wiener Index was 1.43 while The Reciprocal Simpson Index was 2.93.The richness index (The Margalef Index) was 2.03. The Equitability Index was 0.59. In term of feeding guild, most speciesbelong to insectivore (45.45%) and granivore (36.36%) while the rest were piscivore/insectivore and granivore/insectivore.However, the granivore recorded the highest number of individuals (112 or 80.58%) compared to other guilds. Presence of arelatively high diversity of bird species with varieties of feeding guilds indicated that aerobic rice does provide an attractivehabitat or foraging site for avian fauna.